Structural Barriers and Inclusive Solutions to Urban Isolation - Yani, Ahmad; Sudirman (Yayasan Sinergi Kawula Muda, 2025)
Urban social isolation has emerged as a pressing global public health concern, driven by the interplay of social, psychological, and environmental determinants. This narrative review aims to synthesize contemporary evidence on the causes, impacts, and mitigation strategies for social isolation in urban settings. The literature was collected from PubMed, Scopus, and Google Scholar using a combination of keywords related to social isolation, urban design, and community psychology. Inclusion criteria emphasized peer-reviewed empirical studies focused on urban populations, with a preference for mixed-method and interdisciplinary approaches. Findings reveal that fragmented community networks, psychological distress, and inadequate access to safe and inclusive public spaces consistently exacerbate urban isolation. Vulnerable populations—particularly the elderly, migrants, and LGBTQIA+ individuals—are disproportionately affected, often facing systemic barriers such as economic inequality, housing insecurity, and social exclusion. The review underscores the role of participatory community interventions, equitable urban planning, and policy integration in addressing the root causes of isolation. Global best practices demonstrate that inclusive urban infrastructure, cross-sector collaboration, and technology-enabled outreach can significantly enhance social connectivity. This review concludes that urban social isolation must be tackled through systemic reforms, locally tailored interventions, and inclusive public policies. Recommendations for future research include longitudinal studies and mixed-method evaluations that account for intersectional identities and structural inequities. The synthesis offers a holistic framework to guide policymakers, practitioners, and researchers in developing sustainable urban communities that prioritize social cohesion and mental well-being.